Rh(iii)-catalysed C–H/C–H cross-coupling of S-aryl sulfoximines with thiophenes: facile access to [1]benzothieno[3, 2-b][1]benzothiophene (BTBT) and benzothiazines. Issue 57 (24th June 2022) - Yang, Chengyong; Liu, Zheng; Cheng, Rui; Du, Jiping; Ran, Chunhao; Wu, Di; Lan, Jingbo
Abstract : Rhodium-catalysed oxidative C–H/C–H cross-coupling of S -aryl sulfoximines with thiophenes has been accomplished for the first time via a chelation-assisted strategy, which provides an efficient approach to forge BTBT and benzothiazines. Abstract : Reported herein is rhodium-catalysed oxidative C–H/C–H cross-coupling of S -aryl sulfoximines with thiophenes via a chelation-assisted strategy, which provides an efficient approach for the construction of [1]benzothieno[3, 2- b ][1]benzothiophene (BTBT) and benzothiazine skeletons from easily available substrates. This protocol exhibits a good compatibility with halogen substituents, thus paving the way for further transformation to prepare various organic functional molecules. The resulting benzothiazine derivative shows a deep blue emission with Commission Internationale de 'Eclairage (CIE) coordinates of (0.15, 0.04), a high quantum yield, and a delayed fluorescence lifetime.